2021
DOI: 10.3390/su13126610
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of Pedestrian–Motor Vehicle Crashes in San Antonio, Texas

Abstract: Pedestrian safety is becoming a global concern and an understanding of the contributing factors to severe pedestrian crashes is crucial. This study analyzed crash data for San Antonio, TX, over a six-year period to understand the effects of pedestrian–vehicle crash-related variables on pedestrian injury severity based on the party at fault and to identify high-risk locations. Bivariate analysis and logistic regression were used to identify the most significant predictors of severe pedestrian crashes. High-risk… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
20
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 20 publications
(21 citation statements)
references
References 63 publications
1
20
0
Order By: Relevance
“…Nighttime during weekend period had a substantially high severe injury risk, probably due to the higher frequency of DWI and distracted drivers [33], encouraging the use of ridesharing services during this period. Bicyclists exhibited reduced faulty behavior during the weekend, whereas the proportion of faulty motor vehicle drivers of San Antonio was greater during the weekend [44].…”
Section: Discussionmentioning
confidence: 94%
See 2 more Smart Citations
“…Nighttime during weekend period had a substantially high severe injury risk, probably due to the higher frequency of DWI and distracted drivers [33], encouraging the use of ridesharing services during this period. Bicyclists exhibited reduced faulty behavior during the weekend, whereas the proportion of faulty motor vehicle drivers of San Antonio was greater during the weekend [44].…”
Section: Discussionmentioning
confidence: 94%
“…where Y1, Y2, Y3, Y4, and Y5 represent the total number of crashes involving a fatality, serious injury, non-serious injury, possible injury, and no injury, respectively. Bicycle-motor vehicle crash-associated variables selected for statistical analyses (Table 1) were based on a literature review [12,30,33,39,40,[42][43][44]55] to study their effect on the severity of bicycle crashes as stand-alone variables and in conjunction with other. Bivariate analysis is utilized as an exploratory tool for hypothesis of the association test between a dependent and an independent variable, and it was used in this study to explore the relationships between the bicyclist injury severity and bicycle-motor vehicle crash-associated variables (as standalone variables).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Two lane rural roads crash records (about 55,700 crash cases) of the state of Texas collected over a two year period (2017-2018), provided by the Texas Department of Transportation (TxDOT), are used in this paper [39,40]. According to the necessary information for the calculation of the SAA provided by police and other supplemental sources, the crash dataset is classified to four lighting conditions, namely, daylight, dark, dark lit and twilight.…”
Section: Datamentioning
confidence: 99%
“…According to the literature, pedestrian crashes and their severity are influenced by several crash variables (12). Some of these variables are related to pedestrian demographics (age, gender, alcohol use, actions, primary contributing factors), driver demographics (age, gender, condition, violation type), roadway features (number of lanes, posted speed limits, intersection presence, functional classification), and other factors such as land-use pattern, day of the week, weather, and lighting condition (13)(14)(15)(16). Ferguson et al reported that poor lighting conditions combined with alcohol intake by pedestrians and high speed limits on limited-access routes were found to greatly exacerbate the risk of pedestrian injury severity (17).…”
Section: Pedestrian Crash Risk Factors Under Different Lighting Condi...mentioning
confidence: 99%